2015
DOI: 10.3109/09638288.2015.1075608
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of water-based and land-based core stability exercises in patients with lumbar disc herniation: a pilot study

Abstract: An 8-week core stabilization program performed in water or on land decrease pain level and improve functional status in LDH patients. Both programs seem beneficial to increase health-related quality of life and static endurance of trunk muscles. Core stability exercises could be performed in water as well, no differences were found between methods due to environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 30 publications
2
33
0
2
Order By: Relevance
“…Based on the consideration of 30% improvement as a threshold for MCID, most of the SF-36 domain scores meet this threshold. In agreement with our results, Bayraktar et al [ 16 ] showed that healthrelated quality of life, which was measured by Nottingham Health Profile, improved in patients with CLBP due to lumbar disc herniation in both water- and land-based core stability exercise groups. Further, Ota et al [ 32 ] reported improvement in quality of life, based on Japanese Orthopedic Association Back Pain Evaluation Questionnaire, after 3 and 6 months of lumbar stabilization exercises in patients with CLBP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the consideration of 30% improvement as a threshold for MCID, most of the SF-36 domain scores meet this threshold. In agreement with our results, Bayraktar et al [ 16 ] showed that healthrelated quality of life, which was measured by Nottingham Health Profile, improved in patients with CLBP due to lumbar disc herniation in both water- and land-based core stability exercise groups. Further, Ota et al [ 32 ] reported improvement in quality of life, based on Japanese Orthopedic Association Back Pain Evaluation Questionnaire, after 3 and 6 months of lumbar stabilization exercises in patients with CLBP.…”
Section: Discussionsupporting
confidence: 93%
“…In the intervention group, the RDQ score decreased by 5 scores, which was significant. In addition, Bayraktar et al [ 16 ] revealed that patients with CLBP who participated in land- and water-based core stability exercises reported improvement of 5 and 4.5 units in RDQ scores, respectively. As discussed above, most studies have demonstrated the effectiveness of core stability exercises in the amelioration of disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water-based group demonstrated greater improvement in these two measures compared with the land group (F 2 ) ( Table 2). Similar to the results of the present study, some other studies also revealed the effectiveness of exercising in water [12,17,20], in contradiction to others that found no difference between land-based and water-based exercise [18,19,28].…”
Section: Resultssupporting
confidence: 75%
“…In the intervention group, the RMDQ score decreased five points, which was significant (26). Furthermore, Bayraktar et al (27) revealed that LBP patients who participated in land and water CORE stability exercises reported an improvement of 5 and 4.5 points in the RMDQ scores, respectively. Regarding the functional level assessed through ODI, the present study demonstrated a significant reduction of scores in all intervention groups.…”
Section: Discussionmentioning
confidence: 94%